2020
DOI: 10.1146/annurev-biochem-011520-104722
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint Responses to DNA Double-Strand Breaks

Abstract: Cells confront DNA damage in every cell cycle. Among the most deleterious types of DNA damage are DNA double-strand breaks (DSBs), which can cause cell lethality if unrepaired or cancers if improperly repaired. In response to DNA DSBs, cells activate a complex DNA damage checkpoint (DDC) response that arrests the cell cycle, reprograms gene expression, and mobilizes DNA repair factors to prevent the inheritance of unrepaired and broken chromosomes. Here we examine the DDC, induced by DNA DSBs, in the budding y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(116 citation statements)
references
References 240 publications
2
114
0
Order By: Relevance
“…Although we know a great deal about the evolutionarily related phosphoinositol-3-kinase like kinases ATM and ATR, including their structure and phosphorylation targets (29), the manner by which these kinases reach their targets have not been well characterized. In this paper, we used Bayesian model selection to distinguish how Mec1 and Tel1 are able to create extended regions of -H2AX after DNA damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we know a great deal about the evolutionarily related phosphoinositol-3-kinase like kinases ATM and ATR, including their structure and phosphorylation targets (29), the manner by which these kinases reach their targets have not been well characterized. In this paper, we used Bayesian model selection to distinguish how Mec1 and Tel1 are able to create extended regions of -H2AX after DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Results similar to 1D sliding would also be predicted if chromatin near a DSB were actively extruded into a loop, a process different from the looping model in which the chromosome only undergoes passive looping due to thermal fluctuations. In vitro experiments have shown that chromatin can be actively pulled through the ring-shaped cohesin or condensin complexes, resulting in extruded chromatin loops that grow over time (29,30). Indeed, in yeast, cohesin and another SMC complex, Smc5,6 are recruited to sites of DSB damage (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell cycle checkpoints arrest the self-replication process and increase the chances of survival when a cell encounters errors. 4,10,11 However, checkpoints show more complex behaviors than merely gating the cell cycle depending on the presence or absence of errors. After prolonged arrests, checkpoints such as the DNA damage checkpoint or the spindle assembly checkpoint (SAC) are overridden in the continued presence of errors, which is associated with genomic instability and aneuploidy in yeast and mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments support the existence of a balance between risk and speed qualitatively: Budding yeast cells with dysfunctional DNA damage (rad9∆) or spindle assembly checkpoints (mad2∆), which arrest very briefly 4 or not noticeably 10 , die at much higher rates in the presence of DNA damage or poor spindle-chromosome binding. 10 Multiple experimental challenges have to be overcome in order to resolve checkpoint strategies more quantitatively:…”
mentioning
confidence: 99%